"Manejo de residuos bio y no biodegradables en la universidad técnica Estatal de Quevedo, plan piloto educación año 2009. - Real Goya, Gustavo Enrique (2010)
The State Technical University of Quevedo, institution of higher education located in Quevedo, Province of Los Ríos with 26 years of creation has approximately with a population of seven thousand six hundred people formed by students, teachers, employees and workers, which at present date have not incorporated in their daily work any system of collection of waste or use of materials that could be reused as recycling sheets, ink cartridge refills, among others. In visits to large cities such as Guayaquil and Quito, noted that the Municipalities of these cities have implemented in places strategic the placement of containers that allow the selection and collection trash in an organized and scientific way. The exposed antecedents served as support to choose the subject of this field work, which was considered a quality contribution for the UTEQ implement this waste management system, unique in the city and that will be considered as a pilot plan so that if possible it is taken as a model in educational, private, public or other institutions. Any activity or work of an institution generates the use of resources or raw material, these after a process are transformed into waste and they must necessarily be discarded. This bio and non-biodegradable waste is what we commonly call garbage, and it is waste management that is intended to be established within the UTEQ, therefore, the study we present is a proposed solution to a problem that needs urgent attention from the authorities and managers of this institution. .................................................. ...............................................